Land-rich economies, education and economic development - Galiani, Sebastián (2005)
We analyze the emergence of large-scale education systems in a setup where growth is associated with changes in the configuration of the economy. The model is based on three central elements: first, individual preferences over consumption goods generate changes in the composition of individual spending as income grows, embodied in Engel curves. Second, the production of sophisticated services is intensive in human capital. Third, investment in human capital by individual households faces borrowing constraints. Our model uses an overlapping generation framework similar to the one in Galor and Moav (2003). As that paper does, we also model the incentives that the economic ´elite may have (collectively) to accept taxation destined to finance the education of credit-constrained workers. In our model this incentive does not necessarily arise from a complementarity between physical and human capital in manufacturing. Rather, we emphasize the demand for human-capital-intensive services by high-income groups. The argument model seems capable to account for salient features of the development of Latin America in the 19th century, where, in particular, land-rich countries such as Argentina established an extensive public education system and a sophisticated service sector before developing significant manufacturing activities.